A Pedological Characterization of the Black Soils on Trappean Rocks of Indore - Banerjee, S.P. (Journal of Soil and Water Conservation, 2022)
The black soils of India, known as regurs, form a distinct soil group in Indian soil pattern and extends over one-sixth of the total area of the country. Dark coloured soils of apparently similar nature are widely distributed on the surface of the globe at places far apart developed under more or less identical set of pedagogical conditions undertain by various types of geological formations. In India, the black soils mainly overlie the Deccan trap formation but, in addition, they are found to an appreciable extent over the surrounding granites, basic gneisses and sedimentary formations like calcareous shales, limestone’s, slates, sandstones and so on (Wadia, 1945).